2010
DOI: 10.1890/10-0118
|View full text |Cite
|
Sign up to set email alerts
|

Seabird islands take mere decades to recover following rat eradication

Abstract: Abstract. Islands house a majority of the world's biodiversity and are thus critical for biodiversity conservation. Seabird nesting colonies provide nutrients that are integral to maintain island biodiversity and ecosystem function. Invasive rats destroy seabird colonies and thus the island ecosystems that depend on seabird-derived nutrients. After rat eradication, it is unclear how long ecosystem recovery may take, although some speculate on the order of centuries. I looked at ecosystem recovery along a chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 3 publications
1
33
0
Order By: Relevance
“…In Kenya, fishers' catches and income strongly increased after the establishment of closed areas combined with beach seine bans [9,49]. In some cases, marine recoveries can even benefit terrestrial ecosystems, as in the recovery of seabird colonies that enhance biodiversity and functions of island ecosystems by supplying essential marine-derived nitrogen (Figure 3d) [17]. Only a few marine ecosystems, such as Monterey Bay, California [70], have so far shown strong recovery in their structure, function and services over a large area.…”
Section: Species Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, fishers' catches and income strongly increased after the establishment of closed areas combined with beach seine bans [9,49]. In some cases, marine recoveries can even benefit terrestrial ecosystems, as in the recovery of seabird colonies that enhance biodiversity and functions of island ecosystems by supplying essential marine-derived nitrogen (Figure 3d) [17]. Only a few marine ecosystems, such as Monterey Bay, California [70], have so far shown strong recovery in their structure, function and services over a large area.…”
Section: Species Diversitymentioning
confidence: 99%
“…Similarly, many coastal habitats, including wetlands, seagrass beds, mangrove and kelp forests, and oyster and coral reefs, have been severely reduced or degraded [2][3][4]6], yet partial recovery has been achieved in some regions in response to protection and pollution controls [3,13]. Restoration attempts at an ecosystem level have often been followed by the return and recovery of former species assemblages and ecosystem functions [13][14][15][16][17], but some ecosystems have remained in an altered state [18]. Such successes could serve as important guides for efforts to prevent further biodiversity loss and enhance future recoveries.…”
mentioning
confidence: 99%
“…Of these, eradication is the preferable and most effective management option from an ecological standpoint [60]. At least 1,224 successful eradications of invasive species have now been completed on 808 islands around the world [61] and there is good evidence that seabird populations can rapidly recover after the rodents have been removed [62].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…We found that mean burrow density on restored islands was less than half (<0.1 burrow/m 2 ) that on the never-invaded Ruamaahuanui (>0.2 burrow/m 2 ). Thus, although increases in the number of burrows after rat eradication may seem rapid, burrow densities on restored islands have probably not yet reached a level where seabird-dominated ecosystem functioning is possible (Jones 2010b).…”
Section: Conservation Implicationsmentioning
confidence: 99%